FAKTOR-FAKTOR YANG MEMPENGARUHI CASH DIVIDEND PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DIBURSA EFEK INDONESIA - MUHAMMAD SEPTIAN ADITYA; YANA ULFAH; MUHAMMAD IKBAL (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2016)
The purpose of this research is to examine and analyze the influence of fundamental analysis that projected with variable current ratio, return on investment, total asset turnover and earning per share cash dividend against manufacturing companies listed on the indonesia stock exchange period 2010 to 2014. The research of the variable becomes an indicator of fundamental analysis is the current ratio, return on investment, total asset turnover and earning per share (X) against cash dividend (Y). Research data is secondary data obtained from the Indonesian Stock Exchange (www.idx.co.id). Data analysis techniques used multiple linear regression. The population in this research is the annual financial report of the manufacturing companies listed on the Indonesia stock exchange period 2010-2014. Method of determination of the sample determined in Purposive Sampling, and based on the criteria that was specified then the total sample as many as 35 annual report.The results showed that current ratio (CR) and the return on investment (ROI) do not affect significantly to cash dividend while the total asset turnover (TATO) and earning per share (EPS) effect significantly to cash dividend.Keywords: Cash dividend, Current Ratio, Return On Investment, Total Asset Turn Over, Earning Per Share